Learning Supervision as Implementation of Learning Leadership at MTs Nurul Huda Bogor City - Gunarti Sukriyatun (LPPM Institut Nasional Laa Roiba Bogor, 2022)
Teachers as determinants of the success of the learning process in schools/madrasahs have a very important role. In its activities the teacher must carry out several efforts so that the planned learning objectives are achieved. Various plans and preparations made in the learning process must be evaluated programmatically and continuously. One of the evaluation methods is the supervision of learning carried out by the principal/madrasah. With the supervision of learning, it is possible to know the problems that arise as well as find ways to solve the problems that exist in learning. Learning supervision is carried out as well as the implementation of learning leadership carried out by the principal/madrasah. From the results of the performance assessment of the head of Madrasah Tsanawiyah (MTs) Nurul Huda Bogor City, it was found that the supervision of teachers and education staff obtained a score of 42 out of a maximum score of 44 or 95.45%. The performance indicators of the head of madrasa in carrying out supervision are met with complete data support. Thus efforts to make changes in learning towards improvement will be realized. Keyword: supervision; learning; Islamic school; leadership.